Minimal processing of langka (Artocarpus integra Linn) - Los Baños, Raquel Marie E.
The development of minimally processed fresh langka bulbs in passive modified atmospheric packaging was done in this experiment to standardize the postharvest handling of the fruit, to know the most suitable packaging film and temperature condition at which the shelf-life of the product is extended, and to assess the physico-chemical characteristics and sensory attributes of the product. Phase 1 dealt with the selection of the Sinaba fruit and its freshness and maturity indices were observed. Langka was harvested manually at its rare-ripe stage and was without any manifestations of bruising and rotting, or pest attacks. The fruit is firm, slightly aromatic, and has pale yellow bulbs. The total recovery of the fresh langka bulbs was at 37.06%. Phase II involved the packaging and cold storage temperature treatments of 108 trays of fresh langka bulbs. These were divided into 2 groups. In each group were three lots. Each lot of trays were wrapped with 0.005mm linear low density polyethylene (LLDPE), 0.001mm low density polyethylene (LDPE), and 0.001mm polypropylene (PP). The two groups of trays were then subjected to two temperature storage, refrigeration (5°C) and freezing temperature (-18°C). Phase III dealt with the physico-chemical analysis and sensory evaluation of minimally processed langka bulbs taken for 14 days at 2-day intervals, except for the determination of moisture content which was done at 5-day intervals. Samples stored at refrigeration temperature got spoiled after the 10th day of storage period due to the manifestation of fermentation. The increase in moisture content was significantly affected by storage time, packaging, and temperature storage. The titratable acidity of minimally processed fresh langka bulbs had a decreasing trend and was affected by storage time and temperature, but the type of packaging material used did not have a significant effect in the changes of the titratable acidity values. For total soluble solids content, colour and texture, there was no significant effect by storage time, packaging, and cold temperature storage of the fresh langka bulbs in the changes observed. These changes were attributed to the natural ripening reaction of the fresh langka bulbs. The pH values showed increasing and then decreasing trend and were significantly affected by storage time, packaging and temperature storage. For sensory evaluation, minimally processed fresh langka bulbs were evaluated by 30 panelists using Hedonic scale scoresheets. The appearance attribute of minimally processed fresh langka bulbs ranged from firm but tender to slightly firm and the changes in the values were not significantly affected by storage time, temperature and packaging. The colour, integrity, texture, degree of spoilage, sweetness and over-all acceptability of langka were not significantly affected by packaging, but significantly affected by storage time and temperature. Langka was assessed as golden yellow to slightly brownish yellow. The integrity of the fruit bulbs ranged from intact to slightly intact. The texture of minimally processed langka bulbs was ranked to be slightly soft to slightly firm with a fluctuating trend in values throughout the storage period. For the degree of spoilage, the fruit was assessed to have no spoiled smell or taste to a slight presence in spoiled odour. Minimally processed fresh langka bulbs were assessed to be slightly sweet to moderately sweet. For over-all acceptability, minimally processed fresh langka bulbs was assessed to be slightly disliked to slightly liked. Samples wrapped with PP and stored at freezing temperature showed favorable physico-chemical and sensory properties, and exhibited longer shelf-life.